2008
DOI: 10.1166/jnn.2008.221
|View full text |Cite
|
Sign up to set email alerts
|

Layer-by-Layer Self-Assembly of Oppositely Charged Ag Nanoparticles on Silica Microspheres for Trace Analysis of Aqueous Solutions Using Surface-Enhanced Raman Scattering

Abstract: A layer-by-layer (LbL) self-assembly strategy involving oppositely charged Ag nanoparticles was used to deposit a nanoshell of Ag nanoparticles on silica microspheres for trace chemical measurements in aqueous solutions by means of surface-enhanced Raman scattering (SERS). Positively charged Ag nanoparticles were produced by reduction of Ag nitrate in a solution mixture of branched polyethyleneimine (BPEI) and N-(2-hydroxyethyl)piperazine-N'-2-ethanesulfonic acid (HEPES) under UV irradiation whereas negatively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…The ''linkers'' generally used for non-covalent self-assembly are organic polymers 44 and polymer dendrimers, 38,45 DNAs, 37 and proteins; 42,43 as for covalent self-assembly, organic silane 32 and dithiols [33][34][35] are common choices. The preparation of positively charged Ag NPs 46 and their application in the multi-layer self-assembly of oppositely charged NPs as SERS substrates 47,48 has also been reported. The bottom-up approach, however, commonly provides less spatial and sample-to-sample reproducibility than the nanolithographic methods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ''linkers'' generally used for non-covalent self-assembly are organic polymers 44 and polymer dendrimers, 38,45 DNAs, 37 and proteins; 42,43 as for covalent self-assembly, organic silane 32 and dithiols [33][34][35] are common choices. The preparation of positively charged Ag NPs 46 and their application in the multi-layer self-assembly of oppositely charged NPs as SERS substrates 47,48 has also been reported. The bottom-up approach, however, commonly provides less spatial and sample-to-sample reproducibility than the nanolithographic methods.…”
Section: Introductionmentioning
confidence: 99%
“…Alternative approaches for Ag immobilization include thiolexchange reactions 49 and layer-by-layer deposition through electrostatic interactions. 37,38,40,47,48 The limited success of the application of dithiol as a linker to the fabrication of selfassembled Ag structures is probably due to the strong affinity of the thiol functionality towards the Ag surface which favors the simultaneous interaction of both thiol groups of the dithiol with the Ag, leaving no free thiol group to interact with the adjacent layer. 50 Hydrolyzation of MPTMS leads to the formation of a sol-gel rich in free thiol functionalities, 51 which guarantees the availability of thiol groups after binding to the bottom layer of Ag NPs.…”
Section: Introductionmentioning
confidence: 99%
“…Different synthetic strategies have been already proposed to design robust raspberry-like nanoarchitectures, including seed-mediated growth or self-assembly of pre-formed colloidal particles. [8][9][10][15][16][17][18][19][20] Metallic nanoparticle adhesion onto the surface of the dielectric spherical core can be driven by a variety of forces such as electrostatic interactions, 8,15,18,19 covalent bonding 16,17,20 and bio-mediated attraction. 9,21 In most reports, the self-assembly methods were efficient for a certain range of particle sizes, specifically for a core/satellite diameter ratio close to or above 10.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Han et al has demonstrated silver nanoparticle-decorated silica microsphere with designed surface charge for favorable SERS detection of charged species. 16 Silver deposition was done through a layer-by-layer assembly. Detection limit up to ppt concentration has been achieved using single SERS active spheres.…”
Section: Introductionmentioning
confidence: 99%